Mewujudkan Good Governance Melalui Penguatan Budaya Birokrasi - Jayadi, Jayadi; Widiantari, Maria Magdalena; Nurchayati, Zulin; Murti, Endang (Universitas Tribhuwana Tungga Dewi, 2024)
Organizational culture in the bureaucratic environment is often one of the problems that hinder the realization of good governance. On the other hand, the organizational culture that develops cannot be separated from the paternalistic Javanese culture. This makes the character of bureaucratic apparatus behavior more textually patterned based on applicable formal provisions. As a result, government officials cannot make decisions when facing obstacles in carrying out their duties, especially those related to public services. This condition can be overcome by providing flexibility for bureaucratic apparatus to be more creative in taking effective and success-oriented actions in carrying out their duties. This research shows the influence of bureaucratic strengthening efforts on the realization of good governance by eliminating unproductive Javanese cultural values so as to improve the quality of public services. The results reveal that an empowered bureaucracy with flexibility and results orientation is able to respond to community needs more quickly and precisely. In addition, the elimination of unproductive values in Javanese culture is proven to encourage innovation and initiative among bureaucratic apparatus, which ultimately improves the efficiency and effectiveness of public services.Budaya organisasi dalam lingkungan birokrasi seringkali menjadi salah satu persoalan yang menghambat terwujudnya pemerintahan yang baik. Di sisi lain, budaya organisasi yang berkembang tidak dapat terlepas dari budaya Jawa yang paternalistis. Ini membuat karakter perilaku aparat birokrasi lebih terpola secara tekstual berdasarkan ketentuan formal yang berlaku. Akibatnya aparatur pemerintah tidak dapat mengambil keputusan apabila menghadapi hambatan dalam pelaksanaan tugas khususnya terkait dengan pelayanan publik. Kondisi ini dapat diatasi dengan memberikan keleluasaan bagi aparat birokrasi untuk lebih kreatif mengambil tindakan-tindakan efektif dan berorientasi pada keberhasilan dalam menjalankan tugas. Penelitian ini menunjukkan adanya pengaruh upaya penguatan birokrasi terhadap perwujudan good governance dengan menghilangkan nilai-nilai budaya Jawa yang tidak produktif sehingga dapat meningkatkan kualitas layanan publik. Hasil penelitian mengungkap bahwa birokrasi yang diberdayakan dengan fleksibilitas dan orientasi pada hasil mampu merespons kebutuhan masyarakat dengan lebih cepat dan tepat. Selain itu, penghapusan nilai-nilai yang tidak produktif dalam budaya Jawa terbukti mendorong inovasi dan inisiatif di kalangan aparat birokrasi, yang pada akhirnya meningkatkan efisiensi dan efektivitas pelayanan publik.